Bayesian analysis of genetic differentiation between populations of the Duroc and Iberian pig breeds - Alves E.; Fernández A.; Barragán C.; Rodríguez C.; Silió L. (5. International Symposium on the Mediterranean Pig, 2007)
Bayesian methods have been proposed for estimating hidden population substructures in closely related populations. A sampling of 64 Duroc and 170 Iberian pigs, assigned to two strains (Torbiscal and Guadyerbas), two red varieties (Retinto, Entrepelado) and one black hairless variety (Lampiño) was genotyped for 36 microsatellites. An optimal partition of only five clusters was estimated, when the previous assignation to six pig groups was taken into account. The analysis without pre-assigned groups showed a more complex partition: (i) most of the Duroc pigs were grouped into the same cluster; (ii) the cluster of greater size included entirely the Entrepelado variety and most of the Retinto and Lampiño pigs; and (iii) the remaining seven clusters grouped pigs from five small isolated herds or from Torbiscal and Guadyerbas closed strains. Genotypes of MC1R coat color gene also revealed a large intercross between black and red Iberian varieties. The future definition of conservation units in the Iberian breed should consider these results.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)